"It takes two to know one" – Tongue protrusion-retraction is only one small facet of early intersubjectivity. (13th December 2017) - Aitken, Kenneth J.
Abstract: Tongue protrusion-retraction is critical to early nutrition but is also a gustatory-olfactory aspect of early infant social behaviour that is, in part, reliant on pre-natal exposure and learning. Most early development is necessarily dyadic and intrinsically associated with other aspects of social functioning.